2018
DOI: 10.1007/s10518-018-00530-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of seismic performances of unconnected pile foundations using dynamic centrifuge tests

Abstract: An unconnected pile foundation allows separation between the lower pile and the pile cap, and it has been proposed as an effective foundation type for reducing the seismic load during strong earthquakes. However, previous quantitative evaluations of unconnected piles with various foundation types and earthquake intensities are inadequate. In this study, the influence of base shaking level and the material of the interposed layer between pile and pile cap on the seismic behaviour of unconnected piles were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…With the gravel cushion, the load-sharing relationship between shallow soils and piles becomes more reasonable than CPRF [20][21]. The settlement of the DPRF is smaller than a shallow foundation [22][23]. Evidence showed that the gravel cushion could also perform as an isolation layer because it can decrease the earthquake energy transferred to the superstructure [22,[24][25] and the inertial forces from the superstructure to the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…With the gravel cushion, the load-sharing relationship between shallow soils and piles becomes more reasonable than CPRF [20][21]. The settlement of the DPRF is smaller than a shallow foundation [22][23]. Evidence showed that the gravel cushion could also perform as an isolation layer because it can decrease the earthquake energy transferred to the superstructure [22,[24][25] and the inertial forces from the superstructure to the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous ground improvement techniques for the rocking shallow foundation have been investigated, such as the integration of micropiles, 40 stone columns, 41 large rigid foundation slabs, 42,43 and unconnected piles—both short 44 and long 45,46 —to reduce or even eliminate the issues associated with soil settlements and permanent foundation rotations. Despite achieving this goal, the absence of energy dissipation—which would otherwise arise from the inelastic behavior of the bridge pier and the soil medium—results in larger inertial forces to the pier as well as larger deck displacements 47,48,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic response of pile foundations and pile-supported structures has been an important subject of study during several decades (see e.g. Kaynia (1982); Kaynia and Kausel (1991); Miura et al (1994); Mylonakis and Gazetas (1999); Blaney and El Naggar (2000); Nikolaou et al (2001); Maeso et al (2005); Escoffier et al (2008); Rovithis et al (2013); Goit et al (2013); Dowling et al (2016); Li et al (2016); Carbonari et al (April 2019); Ha et al (2019) Chatterjee et al (2019); Correia and Pecker (2021)) due to the widespread use of deep foundations and the influence that the dynamic soil-pile-structure interaction (SSI) phenomena can exert on the dynamic and seismic response of the structures (see e.g. Veletsos and Meek (1974); Mylonakis and Nikolaou (1997); Gazetas and Mylonakis (1998); Mylonakis and Gazetas (2000); Stewart et al (1999aStewart et al ( , 1999b; Gerolymos et al (2008); Medina et al (2013); Di Laora and de Sanctis (2013); Pitilakis et al (2014); Medina et al (2015); de Sanctis et al (2015); Sun and Xie (2019)).…”
Section: Introductionmentioning
confidence: 99%